Rationale and design of TRANSITION: a randomized trial of pre-discharge vs. post-discharge initiation of sacubitril/valsartan - Pascual-Figal, Domingo; Wachter, Rolf; Senni, Michele; Belohlavek, Jan; Noè, Adele; Carr, David; Butylin, Dmytro (ESC heart failure, 2018)
AIMS: The prognosis after hospitalization for acute decompensated heart failure (ADHF) remains poor, especially <30 days post-discharge. Evidence-based medications with prognostic impact administered at discharge improve survival and hospital readmission, but robust studies comparing pre-discharge with post-discharge initiation are rare. The PARADIGM-HF trial established sacubitril/valsartan as a new evidence-based therapy in patients with heart failure (HF) and reduced left ventricular ejection fraction (<40%) (rEF). In common with other landmark studies, it enrolled patients who were ambulatory at the time of inclusion. In addition, there is also still limited knowledge of initiation and up-titration of sacubitril/valsartan in ACEi/ARB- naïve patients and in de novo HF with rEF patients. METHODS AND RESULTS: TRANSITION is a multicentre, open-label study in which ~1000 adults hospitalized for ADHF with rEF are randomized to start sacubitril/valsartan in a pre-discharge arm (initiated ≥24 h after haemodynamic stabilization) or a post-discharge arm (initiated within Days 1-14 after discharge). The protocol allows investigators to select the appropriate starting dose and dose adjustments according to clinical circumstances. Over a 10 week treatment period, the primary and secondary objectives assess the feasibility and safety of starting sacubitril/valsartan in-hospital, early after haemodynamic stabilization. Exploratory objectives also include assessment of HF signs and symptoms, readmissions, N-terminal pro-B-type natriuretic peptide and high-sensitivity troponin T levels, and health resource utilization parameters. CONCLUSIONS: TRANSITION will provide new evidence about initiating sacubitril/valsartan following hospitalization for ADHF, occurring either as de novo ADHF or as deterioration of chronic HF, and in patients with or without prior ACEI/ARB therapy. The results of TRANSITION will thus be highly relevant to the management of patients hospitalized for ADHF with rEF.
Keywords: tepový objem; aminobutyráty; Prognosis; Stroke Volume; Humans; lidé středního věku; Middle Aged; akutní nemoc; propuštění pacienta; Acute Disease; funkce levé komory srdeční; znovupřijetí pacienta; prognóza; Aminobutyrates; mužské pohlaví; Tetrazoles; antagonisté receptorů pro angiotenzin; Patient Discharge; výsledek terapie; Drug Administration Schedule; srdeční selhání; Treatment Outcome; Patient Readmission; ženské pohlaví; rozvrh dávkování léků; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; lidé; Heart Failure; Aged; Ventricular Function, Left; senioři; Male; tetrazoly; Angiotensin Receptor Antagonists; Female